Spontaneous Pregnancy in Postoperative Microperforated Hymen: A Case Report - Pribakti Budinurdjaja; Ihya Ridlo Nizomy; Inas Tsurayya Fauziah Lahdimawan (Berkala Kedokteran, 2021)
Abstract: Female genital tract anomalies have important effects on reproductive function, and usually recognized after puberty. The membrane canalization process end to various hymenal forms. Microperforate hymen appears as a partial obstruction depending on its  size. Most often, patient will present with menstrual disorders, dyspareunia, and infertility. The aim of this research was to report a case of spontaneous pregnancy in postoperative microperforated hymen in form of case report. A 27-year-old woman, P0A0, complained of pain during intercouse. Patient had been married for 1,5 years, had reguler menstrual cycles without any contraceptive method, but not conceived yet. Inspection showed an obstructed vaginal introitus with a small opening laterally at 3 o’clock, consistent witn microperforate hymen. During surgery, short vaginal introitus was observed and no vaginal canal was seen. A sound was inserted through a small opening of 1 mm in diameter laterally at 3 o'clock, followed by sufficient incision and excision of the distal vaginal tissue. Interrupted suture of the proximal and distal mucosa was performed. The vaginal portion as well as uterus appeared normal. Postoperative tissue healing was good. A spontaneous pregnancy occurred 56 days after the surgery and a healthy term baby was born by caesarean section. In the case of microperforated hymen, menstrual flow can be normal. The patient complained of dyspareunia or impaired sexual penetration leading to infertility, although the presence of a small opening may allow passage of sperm and spontaneous pregnancy may occur before the surgery. Surgery can reduce psychological stress and improve reproductive function, allowing pregnancy to occur. Keywords:Abstract: Female genital tract anomalies have important effects on reproductive function, and usually recognized after puberty. The membrane canalization process end to various hymenal forms. Microperforate hymen appears as a partial obstruction depending on its  size. Most often, patient will present with menstrual disorders, dyspareunia, and infertility. The aim of this research was to report a case of spontaneous pregnancy in postoperative microperforated hymen in form of case report. A 27-year-old woman, P0A0, complained of pain during intercouse. Patient had been married for 1,5 years, had reguler menstrual cycles without any contraceptive method, but not conceived yet. Inspection showed an obstructed vaginal introitus with a small opening laterally at 3 o’clock, consistent witn microperforate hymen. During surgery, short vaginal introitus was observed and no vaginal canal was seen. A sound was inserted through a small opening of 1 mm in diameter laterally at 3 o'clock, followed by sufficient incision and excision of the distal vaginal tissue. Interrupted suture of the proximal and distal mucosa was performed. The vaginal portion as well as uterus appeared normal. Postoperative tissue healing was good. A spontaneous pregnancy occurred 56 days after the surgery and a healthy term baby was born by caesarean section. In the case of microperforated hymen, menstrual flow can be normal. The patient complained of dyspareunia or impaired sexual penetration leading to infertility, although the presence of a small opening may allow passage of sperm and spontaneous pregnancy may occur before the surgery. Surgery can reduce psychological stress and improve reproductive function, allowing pregnancy to occur. Keywords: hymen, microperforate, infertility, spontaneous pregnancy